Efavirenz is associated with higher bone mass in South African children with HIV. (23rd October 2016) - Arpadi, Stephen M.; Shiau, Stephanie; Strehlau, Renate; Patel, Faeezah; Mbete, Ndileka; McMahon, Donald J.; Kaufman, Jonathan J.; Coovadia, Ashraf; Kuhn, Louise; Yin, Michael T.
Abstract : Background: We investigate if switching from a ritonavir-boosted lopinavir (LPV/r)-based to an efavirenz-based antiretroviral therapy (ART) regimen is associated with beneficial bone development. Methods: The CHANGES Bone Study follows HIV-infected children who participated in a noninferiority randomized trial in Johannesburg, South Africa evaluating the safety and efficacy of preemptive switching to efavirenz ( n = 106) compared with remaining on LPV/r ( n = 113). HIV-uninfected children were also recruited. Whole-body and lumbar spine bone mineral content (BMC) were assessed by dual-energy X-ray absorptiometry at a cross-sectional visit. BMC Z -scores adjusted for sex, age, and height were generated. Physical activity and dietary intake were assessed. CD4 + percentage and viral load were measured. We compared bone indices of HIV-infected with HIV-uninfected children and LPV/r with efavirenz by intent-to-treat. Results: The 219 HIV-infected (52% boys) and 219 HIV-uninfected (55% boys) children were 6.4 and 7.0 years of age, respectively. Mean ART duration for HIV-infected children was 5.7 years. Whole-body BMC Z -score was 0.17 lower for HIV-infected children compared with HIV-uninfected children after adjustment for physical activity, dietary vitamin D and calcium ( P = 0.03). Whole-body BMC Z -score was 0.55 higher for HIV-infected children switched to efavirenz compared with those remaining on LPV/r after adjustment for physical activity, dietary vitamin D and calcium, CD4 + percentage, and viral load ( P < 0.0001). Conclusion: South African HIV-infected children receiving ART have lower bone mass compared with HIV-uninfected controls. Accrued bone mass is positively associated with switching to efavirenz-based ART compared with remaining on LPV/r, providing additional rationale for limiting LPV/r exposure once viral suppression has been achieved.